2013
DOI: 10.1163/22134808-00002435
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Coding of Human Movement Kinematics

Abstract: Although visual perception is dominant on motor perception, control and learning, auditory information can enhance and modulate perceptual as well as motor processes in a multifaceted manner. During last decades new methods of auditory augmentation had been developed with movement sonification as one of the most recent approaches expanding auditory movement information also to usually mute phases of movement. Despite general evidence on the effectiveness of movement sonification in different fields of applied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 29 publications
1
39
1
2
Order By: Relevance
“…Young et al 32 also demonstrated that synthesized footstep sounds are perceptually processed like ecological footstep sounds on stride length, cadence estimations, and adaptation, supporting the concept of real-time kinematic movement sonification used by Effenberg 21 and Effenberg et al 22 Most of the referenced studies mapped the additional acoustics to distal segments or parts of the acting person (hand or hands, 3,39,40,42 feet, 29 pen-tip, 36,37 hands, and feet). 22 In addition, Vinken et al 17 drafted a mapping-concept explicitly referencing the "effectors' endpoint trajectory" (p. 537) and stated: "Movement sonification was used to transform kinematic data of the distal end effector into the acoustic domain" (p. 539).…”
Section: Research Questionmentioning
confidence: 99%
See 2 more Smart Citations
“…Young et al 32 also demonstrated that synthesized footstep sounds are perceptually processed like ecological footstep sounds on stride length, cadence estimations, and adaptation, supporting the concept of real-time kinematic movement sonification used by Effenberg 21 and Effenberg et al 22 Most of the referenced studies mapped the additional acoustics to distal segments or parts of the acting person (hand or hands, 3,39,40,42 feet, 29 pen-tip, 36,37 hands, and feet). 22 In addition, Vinken et al 17 drafted a mapping-concept explicitly referencing the "effectors' endpoint trajectory" (p. 537) and stated: "Movement sonification was used to transform kinematic data of the distal end effector into the acoustic domain" (p. 539).…”
Section: Research Questionmentioning
confidence: 99%
“…The core idea is an auditory coding of movement kinematics, which has already been introduced and investigated by our workgroup . Research on the inherent information of natural movement‐attendant sounds indicates a rich spectrum of different kinds of information, such as for agent identification and discrimination with complex natural movement sounds or even related to temporal deviations in tap dance sequences .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Behavioural effects are especially strong for extensively practiced noisy actions, for example instrumental performance (Taylor & Witt, 2015). Additionally, specific actions can even be identified from their sonified velocity profile alone (Vinken et al, 2013). Summarised, sound and movement are ecologically coupled.…”
Section: Introductionmentioning
confidence: 99%
“…Pitch-based auditory cues provide an informative, intuitive and commonly used approach for representing kinematic and kinetic measurements in human motion [10][11][12]. When used as feedback, audio cues can enhance performance at motor tasks across a variety of contexts including learning a cyclic motion [10,13,14] and interpersonal coordination [2,15,16]-more generally perceptual coupling including other sensory modalities like vision and touch have been shown to enhance interpersonal coordination (see [17] for a review).…”
Section: Introductionmentioning
confidence: 99%